Carney Complex: A Rare Case of Multicentric Cardiac Myxoma Associated with Endocrinopathy. (2nd July 2018) - Saleh, Yehia; Hammad, Basma; Almaghraby, Abdallah; Abdelkarim, Ola; Seleem, Mohamed; Abdelnaby, Mahmoud; Shehata, Hoda; Hammad, Mahmoud; Ramadan, Bassem; Elshafei, Mohamed; Elsharkawy, Eman; Abdel-hay, Mohamed Ayman
Abstract : Carney complex is a rare autosomal dominant disorder characterized by multiple tumors, including cardiac and extracardiac myxomas, skin lesions, and various endocrine disorders. We are reporting a 21-year-old female patient with past surgical history significant for excision of a cutaneous myxoma who presented with multicentric cardiac myxomas involving the four cardiac chambers. She also presented with endocrinal disorders in the form of an enlarged right lobe of the thyroid, hyperthyroid state, and an incidentally noted adrenal cyst; hence, she was diagnosed with carney complex syndrome.